Evaluation of the Usability of Mobile Library Based on Analytic Hierarchy Process: Case of WeChat Library. Issue 2 (2nd April 2020) - Fu, Lijun; He, Qun; Xi, Qingkui
ABSTRACT: This article studies an indicator system to evaluate the usability of WeChat library, which is a special example of a mobile library and communication platform that enables libraries to provide readers various services using the WeChat software. Based on the analysis of WeChat library, the literature survey and Delphi methods were used to determine the usability of evaluation indicators for WeChat library. The analytic hierarchy process was used to calculate the weights of indicators, and an indicator system to evaluate the usability of WeChat libraries was built. This indicator system has three primary indicators and eleven secondary indicators, and passed the consistency test. This usability evaluation system is helpful to construct and develop WeChat library.